A Sustainable Future for all Towards Reduction of Gender-Based-Violence and Femicide in Communities of Learning: A Strategic Perspective - Jacob T. Mofokeng; Lerato Mofokeng; Nozipho Nkosikhona Simelane (UIN Sunan Gunung Djati, 2024)
Given the reality of the prevalence of all forms of violence such as but not limited to physical, sexual assault, domestic violence (DV), verbal abuse, harassment, stalking, child marriage, economic deprivation, survival sex in a form of exploitation in exchange for access to subsistence resources and forced prostitution, psychological violence or gender-based violence and femicide (GBVF). Being a victim of violence in communities of learning has lifelong impacts on education, health, and well-being of victims. Exposure to violence can lead to educational under achievement due to cognitive, emotional, and social problems. It is argued that GBV is the most extreme expression of unequal gender relations in society and one of the most widespread violations of human rights. While GBV disproportionally affects women and girls, it also affects men and boys. These abuses take place all over the world in homes, places of worship, schools, workplaces, and communities. This paper provides an overview of factors leading to GBVF, impact and effects on the victim as well as methods to eliminate its occurrence were revealed by the analysis. Becoming aware of factors contributing to GBVF and strategies to address this scourge can minimise the occurrence of GBVF in learning communities. Understanding the concepts and strategies to prevent the occurrence of GBV can assist learning communities to minimise these incidences.